An Aristotelian view of therapists' practice in multifamily therapy for young adults with severe eating disorders. (June 2019) - Brinchmann, Berit Støre; Moe, Cathrine; Valvik, Mildrid Elisabeth; Balmbra, Steven; Lyngmo, Siri; Skarbø, Tove
Background: Eating disorders are serious conditions which also impact the families of adult patients. There are few qualitative studies of multifamily therapy with adults with severe eating disorders and none concerning the practice of therapists in multifamily therapy. Objectives: The aim of the study is to explore therapists' practice in multifamily therapy. Research design and participants: A grounded theory approach was chosen. Data were collected through participant observation in two multifamily therapy groups and qualitative interviews with the therapists in those groups. Ethical considerations: The study conforms to the principles outlined in the Declaration of Helsinki. All participants in the multifamily therapy groups received information about the research project and signed consent forms. The data are treated confidentially and anonymised. Findings: The core category was identified as 'having many strings to one's bow', consisting of three subcategories: 'planning and readjusting', 'developing as therapist and team' and 'regulating the temperature of the group'. This article discusses the empirical findings in the frame of Aristotelian virtue ethics.